A Revisited Diagnosis of Collagen VI Related Muscular Dystrophy in a Patient with a Novel COL6A2 Variant and 21q22.3 Deletion - Simsek-Kiper, Pelin Ozlem; Oguz, Sumeyra; Ergen, Fatma Bilge; Utine, Gulen Eda; Alikasifoglu, Mehmet; Haliloglu, Goknur (Neuropediatrics, 2020)
The genetic etiology of collagen VI related muscular dystrophies is heterogenous. Genomic deletions in one allele involving COL6A2 or both COL6A1 and COL6A2 unmasking a pathogenic variant in the second nondeleted allele have been described in the etiology. We aimed to report the clinical and molecular findings of a 13-year-old boy with ring chromosome 21 who presented to our clinic with easy fatigability, muscle weakness, and waddling gait. Phenotypic delineation along with chromosomal microarray analysis and DNA sequencing were performed. Affymetrix CytoScan Optima array platform and DNA sequencing revealed a 2,202 kb de novo deletion at 21q22.3, including COL6A1 and COL6A2, and a novel heterozygous variant at position c.2875G > A;p.(Glu959Lys) in COL6A2, respectively. Before his admission to our center, the patient was evaluated for hypotonia elsewhere when he was 15 months old. He was diagnosed with ring chromosome 21 on peripheral blood karyotype analysis; however, no further assessment was performed at that time. He had normal growth with mild dysmorphic facial features, distal laxity, gastrocnemius hypertrophy, proximal muscle weakness, increased lordotic posture with mild flexion contractures at the knees, and gait disturbance. Although the phenotype does not fit into classical Ullrich congenital muscular dystrophies, muscle magnetic resonance imaging (MRI) revealed a complementary pattern consistent with collagen VI related myopathies. Genetic testing confirmed the clinical diagnosis as well. This patient yet represents another example of the effect of large genomic deletions leading to recessive disorders through unmasking a pathogenic variant in the second nondeleted allele.
Keywords: Collagen VI related muscular dystrophy; COL6A1; COL6A2; 21q22.3 deletion